A Speed-Accuracy Tradeoff Hierarchical Model Based on Cognitive Experiment - Guo, Xiaojun; Luo, Zhaosheng; Yu, Xiaofeng (Frontiers in Psychology, 2020)
Most tests are administered within an allocated time. Due to the time limit, examinees might have different trade-offs on different items. In educational testing, the traditional hierarchical model cannot adequately account for the tradeoffs between response time and accuracy. Because of this, some joint models were developed as an extension of the traditional hierarchical model based on covariance. However, they cannot directly reflect the dynamic relationship between response time and accuracy. In contrast, response moderation models took the residual response time as the independent variable of the response model. Nevertheless, the models enlarge the time effect. Alternatively, the speed-accuracy tradeoff model is superior to other experimental models in the speed-accuracy tradeoff experiment. Therefore, this paper incorporates the speed-accuracy tradeoff model with the traditional hierarchical model to establish a speed-accuracy tradeoff hierarchical model. The results demonstrated that the Bayesian Markov chain Monte Carlo (MCMC) algorithm performed well in the speed-accuracy tradeoff hierarchical model of parameters by using simulation. Finally, the deviance information criterion (DIC) more preferred the speed-accuracy tradeoff hierarchical model than other models in empirical data. This means that it is indispensable to add the effect of response time on accuracy, but likewise should limit the effect on the empirical data.